Microbial Contamination, an Increasing Threat to the Consumption of Fresh Fruits and Vegetables in Today’s World - Gadafi Iddrisu Balali; Denis Dekugmen Yar; Vera Gobe Afua Dela; Priscilla Adjei-Kusi (International Journal of Microbiology)
Microbes are found all over the globe with some few exceptions, including sterilized surfaces. They include normal flora that is nonpathogenic, which contribute to the larger percentage, and pathogenic species which are few. Hence, the activities of humans cannot be completely separated from microbes. Thus, many pathogenic microbes have found their way into fresh fruits and vegetables which are a great source of a healthy diet for humans. The growing demand for fresh fruits and vegetables has necessitated larger production. The larger production of vegetables within the shortest possible time to meet the growing demand has placed them at a higher risk of contamination with the pathogenic microbes, making the safety of consumers uncertain. Study of sources of contamination and type of pathogenic etiological agents isolated from fresh fruits and vegetables includes Bacillus cereus, Campylobacter jejuni, Clostridium botulinum, E. coli O157: H7, Listeria monocytogenes, Salmonella spp., Shigella, Staphylococcus, and Vibrio cholera. Several measures have proven to be effective in controlling contamination of microbes and they include the establishment of surveillance systems to monitor the production chain and thoroughly washing vegetables with vinegar water. Saltwater and other washing techniques are effective but caution should be taken to make sure one does not use one cycle of water for washing all vegetables. The consumption of fresh fruits and vegetables is still encouraged by this review but significant measures must be taken to check the safety of these products before consumption.